Analisis Sektor Unggulan Perekonomian Menggunakan Pendekatan Location Quotient - Randi Adrian Saputra; La Ode Muhammad Irsan; Surdin; Wa Ode Yessi Karantina; Septi Widya Atniza (Jurnal Penelitian Pendidikan Geografi, 2023)
Leading sectors are sectors that provide added value, and production, and have a large influence on other economies. This study aims to analyze the leading sectors in the economy in the Konawe Selatan Regency and Kendari City. This type of research is quantitative research using the Location Quotient Analysis method. The data used in this study is secondary data sourced from the Central Statistics, in the form of GRDP data by Business Field based on Constant Prices for 2017-2021. The results showed that the leading sector in the Konawe Selatan Regency is the Mining and Quarrying sector with an average value of LQ=10.42. Whereas in the Kendari City area is the Corporate Services sector with an average value of LQ=3.92.